Communication, cognitive development and behavior in children with Cornelia de Lange Syndrome (CdLS): Preliminary results. Issue 3 (7th February 2014) - Ajmone, Paola Francesca; Rigamonti, Claudia; Dall'Ara, Francesca; Monti, Federico; Vizziello, Paola; Milani, Donatella; Cereda, Anna; Selicorni, Angelo; Costantino, Antonella
<x xml:space="preserve">Abstract</x> In this study, we present preliminary data on cognitive, behavioral and communication domains of individuals with Cornelia de Lange Syndrome (CdLS), collected through a specific protocol combining direct and indirect tools. Seventeen subjects with CdLS were assessed, 2.5‐ to 13.4‐year‐old. Cognitive level of the subjects differed from what previously described in literature, showing more patients with normal or borderline cognitive abilities. We found a relation between severe autistic behavior and comprehension impairments: all children with high CARS score have severe receptive language disability. A correlation was also found between CARS score and ID: high CARS score occurred only in patients with profound levels of ID. Results of this study support the need for a specific assessment protocol tailored for the characteristics of subjects with multiple disabilities, to be able to identify their strengths avoiding the avalanche effect of weaknesses. Most tests on neuropsychological functions have been developed and standardized for typically developing children, and require the integrity of other functions aside the one that is evaluated, determining an underestimation of the level of functioning. This study could be a starting point to develop new models applicable to other genetic syndromes and complex situations; new and wider studies are needed in order to allow a more complete and accurate assessment, thereby ensuring more efficient and family‐centered treatment plans. © 2014 Wiley Periodicals, Inc.